Analisis Keselamatan, Kesehatan Kerja dan Lingkungan (K3L) Pekerja dalam Membangun SMK 3 Kota Bengkulu - Feri Hari Utami; Maria A. Kartawidjaja (UNIVED Press, 2025)
The purpose of identifying post-fire occupational safety is to ensure that a workplace or facility affected by a fire can resume operations safely and effectively. This includes measures to protect workers, prevent further damage, and minimize potential hazards that may arise after a fire. Primary data was obtained by conducting interviews and questionnaires were administered to select project personnel who held supervisory positions. Secondary data refers to information obtained by other individuals from various sources, such as the internet, literature, and previous research, Characteristics of Occupational Safety and Health (OHS) hazards that often arise in construction projects were obtained from literature research and observation, The HIRADC technique has demonstrated efficacy in identifying, evaluating, and categorizing hazards, in addition to ensuring appropriate mitigation strategies.